ASSESSING THE LEVEL OF TRANSIT-ORIENTED DEVELOPMENT (TOD) AT TRANS SEMARANG TRANSIT POINTS - Aisha Sakina Salsabiila (RADJA PUBLIKA, 2026)
Semarang, a major metropolitan city in Indonesia, faces significant transportation challenges, including severe traffic congestion and air pollution, driven by a high societal reliance on private vehicles. In response, the city has implemented the Trans Semarang Bus Rapid Transit (BRT) system and has officially committed to Transit-Oriented Development (TOD) in its planning documents. However, a critical gap exists between this policy ambition and practical implementation, primarily due to a lack of quantitative tools to assess the existing level of TOD at its transit points. This study addresses this gap by developing and applying a comprehensive TOD Index to objectively evaluate the performance of 27 transit points along the Trans Semarang network. The research utilized a GIS-based Spatial Multi-Criteria Analysis (SMCA) approach, initially drawing 13 indicators rooted in the 5Ds TOD framework. A rigorous data suitability analysis, involving Kaiser-Meyer-Olkin (KMO) and Bartlett's tests, refined the model to a final set of 10 statistically robust indicators. Indicators weights were determined objectively using Principal Component Analysis (PCA) to ensure the resulting scores reflected the inherent structure of the spatial data. The results reveal a distinct monocentric spatial pattern of TOD performance, characterized by a concentration of high-scoring transit points within the dense, historic urban core, while stations on the suburban fringe consistently exhibit low TOD scores. A critical finding of this study is the apparent statistical independence among key TOD dimensions: urban form (density, design) was found to be disconnected from land-use diversity and transit service quality. This highlights a fundamental lack of integration in the city's current land-use and transportation planning efforts. Ultimately, this research provides the Semarang City Government with a valuable, data-driven diagnostic tool to identify underperforming areas, prioritize strategic investments, and formulate evidence-based policies. The findings underscore the urgent need for a more integrated approach to planning to achieve the city’s sustainable development goals.